Life, Love and Death in Latin Poetry - Frangoulidis, Stavros A.; Harrison, S. J. (Trends in classics. Supplementary volumes, 2018)
Inspired by Theodore Papanghelis' Propertius: A Hellenistic Poet on Love and Death (1987), this collective volume brings together seventeen contributions, written by an international team of experts, exploring the different ways in which Latin authors and some of their modern readers created narratives of life, love and death. Taken together the papers offer stimulating readings of Latin texts over many centuries, examined in a variety of genres and from various perspectives: poetics and authorial self-fashioning; intertextuality; fiction and 'reality'; gender and queer studies; narratological readings; temporality and aesthetics; genre and meta-genre; structures of the narrative and transgression of boundaries on the ideological and the formalistic level; reception; meta-dramatic and feminist accounts-the female voice. Overall, the articles offer rich insights into the handling and development of these narratives from Classical Greece through Rome up to modern English poetry.